2012
DOI: 10.1029/2011ja017462
|View full text |Cite
|
Sign up to set email alerts
|

Variability of foF2 over Rome and Gibilmanna during three solar cycles (1976‐2000)

Abstract: Hourly validated values of the F2‐layer critical frequency (foF2) recorded at Rome, Italy (geographic coordinates 41.8°N, 12.5°E; geomagnetic coordinates 42.0°N, 93.8°E), and Gibilmanna, Italy (geographic coordinates 37.6°N, 14.0°E; geomagnetic coordinates 38.1°N, 93.6°E), along with the hourly quiet time reference values of foF2 (foF2QTRV) were considered around periods of minimum and maximum solar activity over the years 1976–2000. The foF2 data set was specifically organized in order to obtain an overall tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
(62 reference statements)
1
3
0
Order By: Relevance
“…The behaviour of MUF is very similar to foF2; therefore, the variability of MUF also increases, which is higher at night than during the daytime. The present findings are consistent with those of previous studies (Kouris et al, 1998;Akala et al, 2011;Pietrella et al, 2012) where it was found that increasing solar activity causes decreasing MUF variability and vice versa. In addition, low MUF VR indicates more consistent MUF data, while high MUF VR indicates inconsistent MUF data.…”
Section: Resultssupporting
confidence: 96%
See 2 more Smart Citations
“…The behaviour of MUF is very similar to foF2; therefore, the variability of MUF also increases, which is higher at night than during the daytime. The present findings are consistent with those of previous studies (Kouris et al, 1998;Akala et al, 2011;Pietrella et al, 2012) where it was found that increasing solar activity causes decreasing MUF variability and vice versa. In addition, low MUF VR indicates more consistent MUF data, while high MUF VR indicates inconsistent MUF data.…”
Section: Resultssupporting
confidence: 96%
“…2(a-c) shows the plots of monthly hourly median for 2009 until 2011. Bilitza et al (2004), Akala et al (2010) and Pietrella et al (2012) discovered that variability of foF2/NmF2, MUF and h'F2 are characterized by pre-sunrise and post-sunset peaks; this is due to the steep electron density gradients occasioned by the onset and turn-off of solar ionisation. From Fig.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Figure 3 collects the results for NmF2, which are typical for mid latitudes [Pietrella et al, 2012]. Since the F2-layer provides a large contribution to vTEC, NmF2 and vTEC share similar features concerning diurnal, seasonal, and solar activity variations.…”
Section: Alessio Pignalberi Et Almentioning
confidence: 91%